(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2026)
Bhandara district situated in eastern part of Vidarbha in Maharashtra state of India, is provided with vast diversity includes forest cover, agricultural lands and even wetlands. This supports the livelihood of tribal and rural people in and around the forest areas and are involved in agriculture for their basic needs. Many of these people are well-aware about the traditional knowledge of utilizing wild edible plants. This study was undertaken to compile the hidden indigenous knowledge of wild edible plants and its diversity in the district. The tribal and rural people of the district involved in utilization of wild edible plants are Gond, Rajgond, Halba, Halbi, Pardhi and Holi. In addition to these, many rural communities are also using wild edible plants during food scarcity since long time. Participatory rural appraisal (PRA), semi-structured interviews, and group discussions with tribal elders, traditional healers, and local foragers was carried out to know the maximum number of wild edible plants used in the district. In this study, a total of 77 species, representing 72 genera and 38 families of angiosperms from dicot and monocot were recorded as wild edible plants. The various parts of the plant like, roots, tubers, rhizomes, corms, tender shoots, stems, gums, leaves, aril, receptacle, flowers, fruits, seeds and whole plants were reported as important dietary resources. The outcome of this study underscores the cultural significance, diversity of wild edible plants, its nutritional value and conservation potential. This will also help to conserve floristic biodiversity and sustainable utilization of resources to promote dietary diversity among tribal and rural communities.